2016
DOI: 10.4028/www.scientific.net/amm.861.24
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lightweight Concrete Produced from Plastics Waste - Polystyrene and EVA

Abstract: In this paper, the lightweight concrete made from polystyrene and ethylene vinyl acetate (EVA) waste was studied. EVA waste from footwear industry and waste polystyrene were used as an aggregate in the lightweight concrete. Each of the plastic wastes was used alone (as a sole aggregate) or in combination with the other in a ratio of 1:3, 1:1 and 3:1. The water-cement ratio of 0.50 and the dose of cement – 175 kg·m-3 were used for all mixtures. Test results showed that the bulk density and the thermal conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This was accomplished by subjecting recycled waste plastic flakes to safe gamma radiation doses before grinding them into a soft powder. Additionally, their findings demonstrated that using this practical idea would be environmentally beneficial due to the fact that manufacturing concrete is responsible for 4.5% of global carbon dioxide emissions, Schaefer et al [71]; Gregorova and Unčík [72]; Morsy and Jailany [73]; Li and Chen [74]; Maghfouri et al [75].…”
Section: Impacts Of Recycled Nanoplastics On Concrete's Mechanical Pr...mentioning
confidence: 99%
“…This was accomplished by subjecting recycled waste plastic flakes to safe gamma radiation doses before grinding them into a soft powder. Additionally, their findings demonstrated that using this practical idea would be environmentally beneficial due to the fact that manufacturing concrete is responsible for 4.5% of global carbon dioxide emissions, Schaefer et al [71]; Gregorova and Unčík [72]; Morsy and Jailany [73]; Li and Chen [74]; Maghfouri et al [75].…”
Section: Impacts Of Recycled Nanoplastics On Concrete's Mechanical Pr...mentioning
confidence: 99%
“…Mechanical recycling might be the most commonly used recovery method for post-consumer shoes because of its low cost, simple recycling process, low energy consumption, and wide applicability. By simple cutting, ESW with a relatively large average size, e.g., 3–4 mm, from the footwear industry could be used as a lightweight aggregate substitute in lightweight concrete or mortar. For example, Dulsang et al prepared lightweight concrete with good mechanical and chemical attack-resistant characteristics by using EVA waste with an average size of 4.5 mm instead of the normal aggregate. Others focused on reusing ESW via blending it with other polymer materials, such as rubber, EVA, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It contributed to the impact noise attenuation and reduced the actual specific weight of the subfloor, creating a lighter structural system. Another study used EVA waste from the footwear industry to produce lightweight concrete, demonstrating remarkable results in thermal conductivity, chemical resistance, and water absorption compared to other lightweight concrete containing other polymers [8,9]. EVA wastes' granulometry effects on the mortar as a natural aggregate substitute were also investigated [2].…”
Section: Introductionmentioning
confidence: 99%